Artificial Intelligence In The Workplace: A Systematic Literature Review Of Psychological Impact, Employee Well-Being, And Managerial Implications - Alifia Ainun Rizky (Business Research and Administration Innovation, 2026)
Artificial intelligence (AI) has fundamentally changed the way humans work, interact, and make decisions in organizational settings. This article presents a systematic literature review of empirical research published between 2020 and 2024, focusing on the psychological impact of AI on employees, its implications for workplace well-being, and the challenges and opportunities in human resource management (HRM). Using a qualitative-narrative approach, 30 articles from internationally reputable journals were analyzed using an antecedent-phenomenon-consequence framework. The findings indicate that the adoption of AI in the workplace has a dual impact: on the one hand, it increases efficiency, work engagement, and data-driven decision-making; on the other hand, it raises anxiety, technostress, and fear of job loss. Moderating variables such as trust in AI, career orientation, and psychological resilience play a significant role in determining individual responses to AI-based changes. Theoretical and practical implications for lecturers, managers, and policymakers are discussed in depth.